2019
DOI: 10.3390/healthcare7010037
|View full text |Cite
|
Sign up to set email alerts
|

The Interlinked Rising Epidemic of Insufficient Sleep and Diabetes Mellitus

Abstract: For healthy existence, humans need to spend one-third of their time sleeping. Any qualitative or quantitative disturbances in sleep would result in an increased prevalence of obesity, metabolic disorders, diabetes, cardiovascular diseases, and hypertension. The paper aims to highlight the growing global problem of insufficient sleep and its significant impact on the rising incidence of diabetes mellitus. An extensive literature search was done in all major databases for “insufficient sleep” and “Diabetes Melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 97 publications
(90 reference statements)
4
33
0
1
Order By: Relevance
“…Indeed, sleep duration alone is strongly associated with the development of metabolic syndrome and accounts for a large proportion of the cardiometabolic risk in shift workers (73). Sleep deprivation has also been shown experimentally to reduce insulin sensitivity (60,74) and has been strongly linked to development of obesity (75,76) and diabetes (77). Although the harms of sleep deprivation are manifold, these will not be discussed in detail in the present review.…”
Section: Common Disruptive Factorsmentioning
confidence: 98%
“…Indeed, sleep duration alone is strongly associated with the development of metabolic syndrome and accounts for a large proportion of the cardiometabolic risk in shift workers (73). Sleep deprivation has also been shown experimentally to reduce insulin sensitivity (60,74) and has been strongly linked to development of obesity (75,76) and diabetes (77). Although the harms of sleep deprivation are manifold, these will not be discussed in detail in the present review.…”
Section: Common Disruptive Factorsmentioning
confidence: 98%
“…As glucose levels are directly dependent on food intake, dietary parameters are important for diabetes management. In addition, even with optimal nutrition and exercise for maintaining a certain life rhythm, high blood pressure, obesity, and hyperglycemia can be caused by disturbances in the circadian rhythm (Kagawa, ); mutations in clock genes can cause hypertension and hyperglycemia due to changes in circadian rhythm, whereas chronic sleep disorder has been shown to affect insulin resistance (Chattu et al, ). Therefore, we believe that “adjustment of life rhythms” plays an important role in the fluctuation of blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…I can eat dinner as scheduled". Meals and sleep have been shown to be associated with diabetes, and recent studies demonstrated that regular lifestyle schedules can modify the circadian rhythm and affect blood sugar control as much as the amounts of food and sleep (Chattu, Chattu, Burman, Spence, & Pandi-Perumal, 2019).…”
Section: Factorial Structure Of the Daily Time Management Scale Formentioning
confidence: 99%
“…Diabetes is a recognized as a global epidemic [1]. About 200 million diabetic people are present worldwide.…”
Section: Introductionmentioning
confidence: 99%